Incidence Rates of Posttraumatic Stress Disorder Over a 17‐Year Period in Active Duty Military Service Members. Issue 6 (29th June 2020) - Judkins, Jason L.; Moore, Brian A.; Collette, Tyler L.; Hale, Willie J.; Peterson, Alan L.; Morissette, Sandra B.
Abstract: Posttraumatic stress disorder (PTSD) affects approximately 8% of the general population. The prevalence of PTSD is twice as high in active duty service members and military veterans. Few studies have investigated the incidence rates of PTSD in active duty military personnel. The present study evaluated the incidence of PTSD diagnoses and the differences between demographic factors for service members between 2001 and 2017. Data on 182, 400 active duty service members between 2001 and 2017 were drawn from the Defense Medical Epidemiological Database and examined by sex, age, service branch, military pay grade, marital status, and race. From 2001 to 2017, the incidence rates of PTSD in the active force (per 1, 000 service members) steadily climbed, with a low of 1.24 in 2002 to a high of 12.94 in 2016. Service members most often diagnosed with PTSD were in the U.S. Army, with the enlisted pay grades of E‐5–E‐9, White, married, male, and between 20 and 24 years old. Statistically significant differences, p s < .001, were found between observed and expected counts across all examined demographic variables. The present study is the first to our knowledge to provide a comprehensive examination of PTSD incidence rates in an active duty military population. Resumen: Spanish Abstracts by Asociación Chilena de Estrés Traumático (ACET) Las tasas de incidencia del trastorno de estrés postraumático durante un período de 17 años en miembros del servicio militar activo TASAS DE INCIDENCIA DE TEPT EN MIEMBROS DEL SERVICIO El trastorno por estrés postraumático (TEPT) afecta aproximadamente al 8% de la población general. La prevalencia del TEPT es dos veces mayor en los miembros del servicio activo y los veteranos militares. Pocos estudios han investigado las tasas de incidencia de TEPT en el personal militar en servicio activo. El presente estudio evaluó la incidencia de diagnósticos de TEPT y las diferencias entre los factores demográficos para los miembros del servicio entre 2001 y 2017. Los datos sobre 182, 400 miembros del servicio activo entre 2001 y 2017 se extrajeron de la Base de datos epidemiológica médica de la defensa y se examinaron por sexo, edad, rama de servicio, grado de pago militar, estado civil y raza. De 2001 a 2017, las tasas de incidencia de TEPT en la fuerza activa (por cada 1, 000 miembros del servicio) aumentaron constantemente, con un mínimo de 1.24 en 2002 a un máximo de 12.94 en 2016. Los miembros del servicio con más frecuencia diagnosticados con TEPT estaban en el Ejército de EE. UU., con los grados de pago de alistados de E‐5‐E‐9, blancos, casados, hombres y entre 20 y 24 años. Se encontraron diferencias estadísticamente significativas, ps <.001, entre los recuentos observados y esperados en todas las variables demográficas examinadas. El presente estudio es el primero de nuestro conocimiento en proporcionar un examen completo de las tasas de incidencia de TEPT en un ejército en servicio activo. 抽象: 簡體及繁體中文撮要由亞洲創傷心理研究學會翻譯 JOTS‐19‐0409.R1 Judkins The Incidence Rates of Posttraumatic Stress Disorder Over a 17‐year Period in Active‐Duty Military Service Members Traditional Chinese 標題: 現役軍人17年間的創傷後壓力症發病率 撮要: 創傷後壓力症(PTSD)影響約8％的普遍人口, 而在現役和退役軍人中, PTSD的患病率是一般的兩倍。少有研究調查現役軍人的PTSD發病率。本研究檢視於2001年至2017年服役的軍人其PTSD確診率, 以及人口因素之間的差異。我們從國防醫療流行病學數據庫, 取得182, 400名現役軍人的數據, 檢視他們的性別、年齡、服役支部、軍人工資等級、婚姻狀況和種族。從2001年到2017年, 現役軍人的PTSD發病率 (每1000人) 穩定地上升, 從2002年1.24的低點, 升至2016年12.94的高點。最常被診斷出患PTSD的軍人種類, 為美國陸軍、薪酬等級E‐5至E‐9、白人、已婚、男性、20至24歲。在受檢視的所有觀察及預期計算人口變量中, 有具統計顯著性的差異(ps < .001)。本研究是我們目前所知, 首個針對現役軍人PTSD發病率的全面檢視。 Simplified Chinese 标题: 现役军人17年间的创伤后压力症发病率 撮要: 创伤后压力症(PTSD)影响约8％的普遍人口, 而在现役和退役军人中, PTSD的患病率是一般的两倍。少有研究调查现役军人的PTSD发病率。本研究检视于2001年至2017年服役的军人其PTSD确诊率, 以及人口因素之间的差异。我们从国防医疗流行病学数据库, 取得182, 400名现役军人的数据, 检视他们的性别、年龄、服役支部、军人工资等级、婚姻状况和种族。从2001年到2017年, 现役军人的PTSD发病率 (每1000人) 稳定地上升, 从2002年1.24的低点, 升至2016年12.94的高点。最常被诊断出患PTSD的军人种类, 为美国陆军、薪酬等级E‐5至E‐9、白人、已婚、男性、20至24岁。在受检视的所有观察及预期计算人口变量中, 有具统计显著性的差异(ps < .001)。本研究是我们目前所知, 首个针对现役军人PTSD发病率的全面检视。